MENGOPTIMALKAN PENILAIAN DENGAN LIVEWORKSHEET PADA FLIPPED CLASSROOM DI SD - Nelly Rhosyida; Mahmudah Titi Muanifah; Trisniawati Trisniawati; Rosidah Aliim Hidayat (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
The purpose of this study was to describe the use of a liveworksheet in optimizing the assessment of flipped classrooms in elementary school. This research used a descriptive qualitative approach. This research instrument was a questionnaire. The subjects of this study were 100 teachers from various regions in Indonesia. The results of the study stated that 96% of respondents stated that the liveworksheet media was interesting to use in learning, 91% of respondents said that the liveworksheet could be adjusted to the needs of students at elementary school age. As many as 82% of respondents stated that the use of a liveworksheet could be used for authentic assessment, and 76% of respondents stated that it was easy to use it in learning. Based on this, it could be said that the liveworksheet could be used as an alternative to an online-based assessment tool that was attractive, interactive, easily-accessible, and presented a variety of activities that could be tailored to the characteristics of students